The complexity of defining and assessing the most demanding periods of play in team sports: A current opinion - Lino-Mesquita, J.; Baptista, I.; Nakamura, F. Y.; Casanova, F.; Yousefian, F.; Travassos, B.; Afonso, J. (Strength and Conditioning Journal, 2025)
In the context of training load monitoring, the most demanding periods of play (MDPs) have increasingly caught the interest of researchers. However, the MDPs analysis is currently embryonic, raising some conceptual and methodological questions. This current opinion synthesizes the methods used for the MDPs analysis while highlighting conceptual and methodological gaps and proposing a broader perspective on the topic. It is underlined that (a) the information available on the MDPs is mostly limited to external load (particularly running-based metrics), with scarce research focused on internal load; (b) the metrics have been analyzed in a univariate way, neglecting the multivariate scenarios from which the MDPs emerge; (c) the MDPs are highly variable over time due to the complex interaction between individual, tactical-technical, and contextual factors; and (d) scarce evidence is available regarding the contextualization of the MDPs from a tactical-technical perspective. Thus, the MDPs would benefit from cross-referencing external load with game moments and tactical actions while avoiding the idea of fixed benchmarks given the inherent match-to-match variability. Practitioners may consider replicating the MDPs (and their contexts) in (some?) training sessions as a complementary prescription strategy (metaphorically, the cherry on top, not the cake). However, the feasibility and effectiveness of such practices warrant investigation.